Social Norms and Private Provision of Public Goods: Endogenous Peer Groups - Mari Rege (Statistics Norway, Research Department, 1999)
The formation of peer groups with social norms for private contributions to a public good is analyzed in an n-player two stage game. First people choose a peer group, then they choose whether to contribute. The first choice is made through a learning process represented by evolutionary dynamics, while the second choice is made by utility maximization. The game has two types of stable states: One in which very few people belong to peer groups with social norms for private contributions, and one in which a large portion of people belong to such peer groups. ln the former state nobody contributes, while in the latter everybody contributes. Direct governmental contributions to the public good can move the society to a stable state in which nobody contributes, where as governmental subsidization can move the society to a stable state in which everybody contributes. Indeed, the crowding in caused by subsidization can prevail after policy reversal.
Keywords: D11; H20; H41; 330; crowding in; crowding out; evolution; peer groups; public goods; social norms; social sanctions